2007
DOI: 10.1021/bi700602n
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of a GatCAB Amidotransferase:  Aspartyl-tRNA Synthetase Increases Its Affinity for Asp-tRNAAsn and Novel Aminoacyl-tRNA Analogues Are Competitive Inhibitors

Abstract: The trimeric GatCAB aminoacyl-tRNA amidotransferases catalyze the amidation of Asp-tRNAAsn and/or Glu-tRNAGln to Asn-tRNAAsn and/or Gln-tRNAGln, respectively, in bacteria and archaea lacking an asparaginyl-tRNA synthetase and/or a glutaminyl-tRNA synthetase. The two misacylated tRNA substrates of these amidotransferases are formed by the action of nondiscriminating aspartyl-tRNA synthetases and glutamyl-tRNA synthetases. We report here that the presence of a physiological concentration of a nondiscriminating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 29 publications
2
45
1
Order By: Relevance
“…It is speculated that in vivo complexes between NDaaRSs and AdTs protect the aa-tRNA from deacylation. 22,32,33 The M. thermautotrophicus GatDE utilized both amide donors (Fig. 1a), though it is approximately fivefold more efficient with Asn than Gln as the donor for transamidating Glu-tRNA Gln ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is speculated that in vivo complexes between NDaaRSs and AdTs protect the aa-tRNA from deacylation. 22,32,33 The M. thermautotrophicus GatDE utilized both amide donors (Fig. 1a), though it is approximately fivefold more efficient with Asn than Gln as the donor for transamidating Glu-tRNA Gln ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, in vivo experiments have shown that under certain conditions, the Glu residue of Glu-tRNA Gln can be incorporated into proteins, suggesting that an additional locking mechanism may be needed to prevent translational errors (6,14). Such a mechanism was shown in Pseudomonas aeruginosa and H. pylori , where the channeling of misacylated aa-tRNAs from the ND-aaRS to the aa-tRNA amidotransferase effectively sequesters them (15), as initially suggested by Schön et al (16). Sequestration of misacylated aa-tRNAs through the formation of more robust interactions was then confirmed in thermophilic organisms.…”
Section: Introductionmentioning
confidence: 88%
“…Cells for the overproduction of H. pylori GluRS2 and GatCAB were cultured and lysed as adapted from previous works (6,15). Both enzymes were purified by ion-exchange chromatography on DEAE-cellulose (DE52, Whatman), followed by affinity chromatography on Ni-NTA resin (Novagen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations